Clinical Status and Outcome of Isolated Right Ventricular Hypoplasia: A Systematic Review and Pooled Analysis of Case Reports - Hirono, Keiichi; Origasa, Hideki; Tsuboi, Kaori; Takarada, Shinya; Oguri, Masato; Okabe, Mako; Miyao, Nariaki; Nakaoka, Hideyuki; Ibuki, Keijiro; Ozawa, Sayaka; Ichida, Fukiko (Frontiers in Pediatrics, 2022)
Background: Isolated right ventricular hypoplasia (IRVH), not associated with severe pulmonary or tricuspid valve malformation, is a rare congenital myocardial disease. This study aims to evaluate the clinical status and outcome of IRVH. Methods: A systematic search of keywords on IRVH was conducted. Studies were searched from MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Igaku Chuo Zasshi (Ichushi) published between January 1950 and August 2021. Results: Thirty studies met the inclusion criteria. All of these studies were case reports and included 54 patients (25 males and 29 females). The median age of the patients was 2.5 years old (0–15.3 years). Of the 54 patients, 13 (24.1%) reported a family history of cardiomyopathy. Moreover, 50 (92.6%), 19 (35.2%), and 17 (31.5%) patients were diagnosed with cyanosis, finger clubbing, and dyspnea, respectively. Furthermore, 53 (98.2%) patients had a patent foramen ovale or an atrial septal defect (ASD). Z-score of the tricuspid valve diameter on echocardiogram was -2.16 ± 1.53, concomitant with small right ventricular end-diastolic volume. In addition, 29 (53.7%), 21 (38.9%), 7 (13.0%), and 2 (3.7%) patients underwent surgery, ASD closure, Glenn operation, and one and a half ventricular repair, respectively. Among them, nine (20.4%) patients expired, and the multivariable logistic regression analysis showed that infancy, heart failure, and higher right ventricular end-diastolic pressure were risk factors for death. Conclusions: IRVH was diagnosed early in children with cyanosis and was associated with high mortality. This systematic review and pooled analysis provided evidence to assess the of IRVH degree in order to evaluate the clinical status and outcome of IRVH.